2000
DOI: 10.1016/s0002-9440(10)64794-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rifampin Treatment on Intestinal Expression of Human MRP Transporters

Abstract: The importance of the ATP-dependent transporter P-glycoprotein, which is expressed in the brush border membrane of enterocytes and in other tissues with excretory function, for overall drug disposition is well recognized. For example, induction of intestinal P-glycoprotein by rifampin appears to be the underlying mechanism of decreased plasma concentrations of P-glycoprotein substrates such as digoxin with concomitant rifampin therapy. The contribution of transporter proteins other than P-glycoprotein to drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
147
2
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 266 publications
(155 citation statements)
references
References 41 publications
3
147
2
3
Order By: Relevance
“…Thus, there appear to be species differences in the ability of PXR ligands to induce P-gp in humans and rats. Rifampin treatment induced another member of the ATP-binding cassette transporter family, MRP2 at both the mRNA and protein levels in intact human intestine (Fromm et al, 2000b). This result was extended to primary cultures of human hepatocytes, in which PXR ligands, rifampicin and HIV protease inhibitors, caused a significant increase in MRP2 mRNA level ).…”
Section: Induction Of Multiple Drug Resistance Genes In Ratsmentioning
confidence: 76%
“…Thus, there appear to be species differences in the ability of PXR ligands to induce P-gp in humans and rats. Rifampin treatment induced another member of the ATP-binding cassette transporter family, MRP2 at both the mRNA and protein levels in intact human intestine (Fromm et al, 2000b). This result was extended to primary cultures of human hepatocytes, in which PXR ligands, rifampicin and HIV protease inhibitors, caused a significant increase in MRP2 mRNA level ).…”
Section: Induction Of Multiple Drug Resistance Genes In Ratsmentioning
confidence: 76%
“…It has been found that this sequence also interacts with PXR and the constitutive androstane receptor. Indeed, most of the PXR ligands such as rifampicin and hyperforin have been shown to upregulate MRP2 expression in humans, mice, and rats (Fromm et al 2000, Kast et al 2002, Anapolsky et al 2006. Excess glucocorticoid concentrations increase the MRP2 mRNA levels, which implicates glucocorticoidinducible PXR activation (Kliewer et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The growing list of PXR target genes include, in addition to CYP3A family members, CYP2B6 (Wang et al 2003), Cyp7a1 (cholesterol 7 a-hydroxylase; Staudinger et al 2001), UDP-glucuronosyltransferase 1A1 (Hartley et al 2004), intestinal P-glycoprotein (Geick, Eichelbaum, and Burk 2001), OATP2 (Hartley et al 2004), and MRP2 (Fromm et al 2000).…”
Section: Pxr Phenotypementioning
confidence: 99%